ANALISA KELAYAKAN USAHA DISTRIBUTOR BUAH KELAPA DI BANGETAYU WETAN GENUK SEMARANG - athfal alex al Buntoni; muhammad yusuf (Universitas Muhammadiyah Semarang, 2020)
Potential coconut illustrated from of crop productivity in Central Java as the primary commodity reached 1.2864 million tons in 2015. Cashflow from research object coconut distributor reached Rp. 1.536.678.000/ years. The analyse of activity series composed by organisation structure, distribution plot, product handling. Product diversification, layout, and employe. Value of financial analyse carried out NPV (Net Present Value) 2.056.306.704, value of BC Ratio (Benefit Cost Ratio) 6,23, value of IRR (Internal Rate of Return) 40,16%. This research, if NPV have positif, so haved affect to positif BC Ratio and IRR haved greater value from interest rate so that Musriah coconut bussines keeping worth. Value of payback periode is 0,88, so to recoup only takes 10 month 21 days. Marketing mix contain of 4P with Product 3,69 and Price 3,87. Grade of product and price have a good criteria, cause consumer can fulfilled the expectation. Grade of place is 3,54 and grade of promotion is 3,15. Grade of place and promotion have a good criteria, but needed a repair to be better.